OCCURRENCE OF UNUSUAL HAEMOGLOBINOPATHIES IN BALOCHISTAN: HB SD AND HB SE - PRESENTATION WITH OSTEOMYELITIS - Usman Tauseef; Misbah Anjum; Mohsina Ibrahim; Hina Sabih Baqai; Abubakar Tauseef; Marium Tauseef; Muhammad Sohaib Asghar; Maryam Zafar; Uzma Rasheed; Nimra Shaikh (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To describe two cases of unusual variants of sickle cell disease. Case description: We present two cases of sickle cell disease variants (haemoglobinopathies), from unrelated families, in the state of Balochistan (Pakistan). One was diagnosed with sickle cell disease in the haemoglobin electrophoresis, whereas the other was diagnosed with sickle cell SE disease. Both were diagnosed based on the presentation of osteomyelitis. Comments: Haemoglobin SD disease (Hb SD) and haemoglobin SE disease (Hb SE) are rare haemoglobinopathies in the world. The lack of available literature suggests that both are variants of sickle cell disease (SCD), with heterogeneous nature. The prevalence of sickle cell disease with compound heterozygotes was found at a variable frequency in the population of the Asian Southeast. The frequency of osteomyelitis in SCD is 12 to 18%, but its occurrence among variant haemoglobinopathies is little reported. Both reported cases presented with osteomyelitis as a characteristic of the disease presentation.